UPAYA PENINGKATAN JUMLAH KUNJUNGAN PASIEN DITINJAU DARI SERVICE QUALITY DI KLINIK PRATAMA PELITA KASIH MEDAN TAHUN 2017 - Manaluu, Elisabet; Girsang, Rostiodertina; Hasnita, Evi (Jurnal Inovasi Kesehatan Masyarakat, 2019)
The existence of private health facilities is needed in assisting health services. Health facilities are required to be able to provide quality health services with affordable medical expenses so as to increase the number of patient visits. The purpose of this study is to determine the effort increase of patient visits number that observed from service quality in Clinic of Pratama Pelita Kasih Medan in 2017. This study use cross sectional analytic. The population of this study is all patients who had record and get treatment in Clinic of Pratama Pelita Kasih, Medan, as many as 229 patients and use accidental sampling technique. Data collecting use questionnaire. Data is analyzed by used chi square test and data processing program. The result of research shows that there is significant correlation (the value of p 0,041) between health service quality and patient satisfaction, there is no significant correlation (the value of p=0.653) between health service quality and number of respondent (patient). There was a significant relationship (the value of p=0.021) between satisfaction with the number of respondents (patient). It is suggested that the performance of health services can be improved in order to be able to compete with the clinic of Pratama through the addition of medical personnel (general practitioner, dentist, pediatrician, nerve and geneacologyst), competent paramedical personnel (nurse, midwife, chemical analyst), diagnostic equipments (such as ultrasonograph) and change previous types of medication to more affordable medicines to reduce expensive medical treatment.